Development and evaluation of two brief digital health promotion game booths utilizing augmented reality and motion detection to promote well-being at a gerontechnology summit in Hong Kong - Sit, Shirley Man-Man; Lai, Agnes Yuen-Kwan; Kwok, Tai-on; Wong, Hoi-wa; Wong, Yiu-lun; Chow, Edward; Kwok, Yu-kwong; Wang, Man-Ping; Ho, Sai-Yin; Lam, Tai-Hing (Frontiers in Public Health, 2022)
Background The acceleration of population aging calls for simple and effective interventions catered for older people. Gerontechnology, the combination of gerontology and technology, can promote quality of life in older adults. However, public health-related events incorporating information communication technology (ICT) for older people have seldom been evaluated. Objective We reported the development and evaluation of two simple and brief digital health promotion games hosted at the annual Hong Kong Gerontech and Innovation Expo cum Summit (GIES) in 2018 and 2019 to promote well-being. Methods Two game booths (Dinosaur Augmented Reality photo-taking in 2018, Sit-and-Stand fitness challenge in 2019) were designed by our interdisciplinary team. Four gaming technologies were employed: augmented reality, chroma key (green screen), motion detection and 3D modeling. Immediately after the game, we administered a brief questionnaire survey to assess participant satisfaction, happiness and perceived benefits, and collected qualitative data through observations and informal interviews. Results Majority of 1,186 and 729 game booth participants in 2018 and 2019, respectively, were female (73.4% and 64.7%) and older adults (65.5 and 65.2%). Overall satisfaction toward the game booths was high (4.64 ± 0.60 and 4.54 ± 0.68 out of 5), with females and older adults reporting higher scores. Average personal and family happiness of participants in 2018 were 8.2 and 8.0 (out of 10). 90.3 and 18.4% of participants in 2019 chose one or more personal (e.g. enhance healthy living habits 62.4%, enhance personal happiness 61.6%) and family (e.g. enhance family happiness 15.6%, improve family relationships 10.8%) benefits of the game booth, respectively. Participants showed enthusiasm toward the technologies, and pride in their physical abilities in the fitness challenge. Conclusion Our report on the development and evaluation of brief game interventions with ICT showed high satisfaction and immediate perceived benefits in community participants. Females and older adults reported higher satisfaction. Simple tools measuring happiness and perceived benefits showed positive results. Older adults were receptive and enthusiastic about the new technologies. Our findings can inform researchers and organizers of similar events. More research on simple and enjoyable ICT interventions is needed to attract older adults and promote their well-being. Trial registration The research protocol was registered at the National Institutes of Health (Identifier number: NCT03960372) on May 23, 2019.